Analisis Karakteristik Responden Dalam Penentuan Sistem Irigasi Dalam Organic Urban Farming - Sunik Sunik; Sari Perwita R.I. (BiSTeK Pertanian, 2023)
Urban yards can be used for organic urban farming by growing vegetables without the use of chemicals. By doing this, the need for nutritious and healthy food at the family level can be met. One of the disadvantages of growing vegetables in the yard is neglecting plant care, especially watering. This causes the plants to lack water and the resulting vegetables wilt and even die. A drip irrigation system using either a hose or emitter can be applied to meet plant water needs. However, the characteristics of organic urban farming actors have an impact on the choice of irrigation type applied in their respective yards. Therefore, the aim of this research is to analyze the characteristics of respondents and identify the considerations of respondents in determining the type of irrigation used. The analytical method used is descriptive qualitative. The research results showed that the majority of respondents were of productive age, with the highest level of education being high school, and the type of work was as workers (civil servants, private sector and entrepreneurs). Considerations in determining the type of irrigation are the level of complexity, availability of time, ease of implementation.